2018
DOI: 10.1021/acs.orglett.8b02296
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclopropenethione-Phosphine Ligation for Rapid Biomolecule Labeling

Abstract: Cyclopropenethiones are reported as new bioorthogonal reagents. These motifs react readily with substituted phosphines to provide thiocarbonyl adducts. In some cases, the ligations are >300-fold faster than analogous reactions with bioorthogonal cyclopropenones. Dialkyl cyclopropenethiones are also stable in aqueous buffers and can be used for biomolecule labeling in vitro and in cell lysate. The rapid reactivity and biocompatibility of cyclopropenethiones suggest that they will be useful probes for cellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“… Modifications to the cyclopropenone core can also alter reactivity. For example, we showed that sulfur heteroanalogues (CpS) react more rapidly with substituted phosphines …”
mentioning
confidence: 99%
“… Modifications to the cyclopropenone core can also alter reactivity. For example, we showed that sulfur heteroanalogues (CpS) react more rapidly with substituted phosphines …”
mentioning
confidence: 99%
“…To address this, Prescher and co-workers developed (Scheme 1aii) a series of ligations between a nucleophilecontaining phosphine and a cyclopropenone; these cyclopropenone derivatives furnish faster rates in reactions with phosphines (k 2 � 20 M À 1 s À 1 ). [24][25][26][27] In addition, the relatively small size and stability of cyclopropenones under physiological conditions make them potential candidates for applications in bioorthogonal labelling applications. [28] By varying the nucleophile in the phosphine and the substitution pattern of the cyclopropenone, semi-orthogonal reactivity was observed between two pairs of phosphines and cyclopropenones.…”
Section: Phosphine Ligationsmentioning
confidence: 99%
“…[57] Furthermore, the ligation can be further accelerated by applying cyclopropenethiones instead of cyclopropenones to increase reaction rates by ~300-fold in acetonitrile. [58] Similar to their oxo-analogs, cyclopropenethiones are amenable to in vitro protein labeling; however, the cyclopropenethione derivatives are less stable and will require further development for future applications in living-cell experiments. Nevertheless, this innovative approach nicely demonstrates the versatility and the potential for phosphines in biological applications in addition to Staudingertype reactions.…”
Section: Light-activated Cycloadditionsmentioning
confidence: 99%